RANCANG BANGUN SISTEM INFORMASI PEMASARAN ALAT BANGUNAN PADA TOKO KARYA BERSAMA MENGGUNAKAN METODE LINEAR SEQUENCE - Novia Setiawan; Syafri Arief; Sudirman (JTRISTE, 2017)
This study aims to design a system that can help the Toko Karya Bersama in handling the marketing of building tools, where this research using Linear Sequence method. To obtain data and information that support the implementation of this research, conducted observations and interviews. Information Building Tool Marketing is designed using Data Flow Diagrams (DFD), then implemented using Visual Basic 6.0 and Microsoft Access programming as a data processor, then tested using the Black Box testing method. With this new computer-based system, it is expected that the owner of Toko Karya Bersama can run the marketing process of building tools.